PENGUKURAN DAN PERBANDINGAN NILAI OVERALL EQUIPMENT EFFECTIVENESS (OEE) PADA MESIN SPRING PRESS UNTUK OPTIMALISASI EFISIENSI PRODUKSI SHOCK ABSORBER - M. Adi Saepul Bahri; Supriyati; Setiawan (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2025)
This research aims to compare the OEE values on the Spring Press Auto machine (B6H) and the Spring Press Manual machine (B65) and will analyze the OEE results of the two machines to see whether they comply with world class OEE standard. Quantitative research methods were used to carry out this research. Production performance analysis is important for companies in ensuring the efficiency and effectiveness of their production operations. One technique for assessing production efficiency is OEE.. This approach is utilized to measure how effectively production machines and equipment work in achieving predetermined production targets. This method measures three main things in production operations, namely availability, performance and quality of production machines and equipment. The OEE values obtained on the Spring Press Auto machine (B6H) and the Spring Press Manual machine (B65) still do not reach the world-class OEE standard. To achieve JIPM (Japan Institute of Plant Maintenance) standards, the Shock Absorber machine must achieve a score of 85%.